191k views
0 votes
Please, help me
What is it.

Please, help me What is it.-example-1

2 Answers

3 votes

Answer: 4^12

The rule you use is a^b*a^c = a^(b+c). You add the exponents and keep the base the same. This rule cannot be used if you are multiplying two exponential expressions with different bases.

In this case, a = 4, b = 4, c = 8.

User Jeffz
by
4.9k points
6 votes

Answer:

4^12

Explanation:

4^4 * 4^8

When we are multiplying power with the same base, we can add the powers

a^b * a^c = a^ (b+c)

4^(4+8)

4^12

User Clomp
by
4.9k points